Differential lipids in euthyroid pregnant women with positive TPOAb and its correlation with clinical parameters - Chen, Xinxin; Qin, Yuxin; Wang, Qingyao; Wu, Ying; Zang, Huanhuan; Cong, Xiangguo; Shen, Qiong; Chen, Lei (Frontiers in Endocrinology, 2025)
IntroductionPregnant women with subclinical hypothyroidism or clinical hypothyroidism often exhibit lipid metabolism disorders and are correlated with adverse pregnant outcomes. It was suggested that isolated positive thyroid peroxidase antibody (TPOAb) served as a risk factor for adverse outcomes. However, little was known about the lipid metabolism profile in pregnant women with isolated positive TPOAb. The purpose of this prospective observational study was to investigate the expression of lipid profiles among euthyroid pregnant women with positive TPOAb during there early pregnancy and to analyze their correlation with thyroid function.MethodsNon-targeted liquid chromatography-mass spectrometry (LC-MS) technology was used to perform lipidomics analysis on serum samples collected during early pregnancy from pregnant women who with isolated positive TPOAb and those in the healthy control group. Partial least squares-discriminant analysis (PLS-DA), KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis, and correlation analysis were conducted to explore differential lipid molecules and their associations with clinical parameters.ResultsA total of 90 pregnant women in the first trimester were enrolled in the analysis: 46 were TPOAb-positive euthyroid pregnant women, and 44 were healthy pregnant women. A total of 1238 lipid molecules were identified, and 202 differential lipid molecules were screened between the two groups. KEGG pathway enrichment analysis revealed that the differentially expressed lipids participate in several pathways. Correlation analysis showed LPC(20:4), LPC(18:0), LPC(22:4), LPC(22:5), LPC(18:1), PC(20:1/20:4) were both positively correlated with TPOAb titers and sCD40L. LPC(20:0) was positively correlated with the level of remnant cholesterol (RC) and PC(20:1/20:4) was negatively correlated with RC.DiscussionThe lipid profile of isolated TPOAb-positive euthyroid pregnant women was significantly different from that of healthy pregnant women and involved in several pathways. The pathophysiological role of altered lipid molecules should be further investigated since they might be potential biomarkers for adverse pregnancy outcome in pregnant women with isolated positive TPOAb.